Polymorphism and Genetic Structure of LGB Gene (Rsai) in Valachian Sheep Population - Martina Miluchová; Anna Trakovická; Michal Gábor (Scientific Papers Animal Science and Biotechnologies, 2023)
The work was oriented to identification of beta-lactoglobulin gene (LGB) polymorphism and analysis of genotype structure in population of Valachian sheep. LGB is the major milk whey protein in the ruminants. AA and AB genotypes are associated with protein and casein content and curd yield. BB LGB genotype sheep were characterized by a significantly higher protein content of milk than sheep with the other two LGB genotypes — AA and AB. LGB variant AB is associated with higher body weight, while genotype AA could be linked with sheep wool density. The material involved 34 Valachian sheep. Ovine genomic DNA was isolated by salting out method and used in order to estimate LGB genotypes by PCR-RFLP method. The PCR products were digested with RsaI restriction enzyme. In the population included in the study, we detected all genotypes: homozygote genotype AA (6 animals), heterozygote genotype AB (12 animals) and homozygote genotype BB (16 animals). In the population of sheep homozygotes BB – 0.4706 were the most frequent, while homozygotes AA – 0.1765 were the least frequent ones. This suggests a slight superiority of allele B – 0.6471.